2019
DOI: 10.3390/ijms20112767
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β-Mediated Epithelial-Mesenchymal Transition and Cancer Metastasis

Abstract: Transforming growth factor β (TGF-β) is a secreted cytokine that regulates cell proliferation, migration, and the differentiation of a plethora of different cell types. Consistent with these findings, TGF-β plays a key role in controlling embryogenic development, inflammation, and tissue repair, as well as in maintaining adult tissue homeostasis. TGF-β elicits a broad range of context-dependent cellular responses, and consequently, alterations in TGF-β signaling have been implicated in many diseases, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
597
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 787 publications
(671 citation statements)
references
References 261 publications
(204 reference statements)
16
597
0
2
Order By: Relevance
“…33 Autocrine TGFβ/TGFβR signalling can stimulate the EMT in the cancer cells. 34 Our results also provided the evidence that poFUT1, epiregulin and uPA were expressed at lower levels in trophoblast from abortion patients ( Figure 1A Epiregulin is secreted by early human placenta and uterine glands. [9][10][11] Epiregulin is a member of the EGF family, which are involved in many physiological and pathological processes, such as oocyte maturation, cutaneous wound healing and vascular remodelling.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…33 Autocrine TGFβ/TGFβR signalling can stimulate the EMT in the cancer cells. 34 Our results also provided the evidence that poFUT1, epiregulin and uPA were expressed at lower levels in trophoblast from abortion patients ( Figure 1A Epiregulin is secreted by early human placenta and uterine glands. [9][10][11] Epiregulin is a member of the EGF family, which are involved in many physiological and pathological processes, such as oocyte maturation, cutaneous wound healing and vascular remodelling.…”
Section: Discussionsupporting
confidence: 71%
“…MMP14 activation is critical for EMT and migration by regulating the levels of cadherins in the cells . Autocrine TGFβ/TGFβR signalling can stimulate the EMT in the cancer cells . Our results also provided the evidence that poFUT1, epiregulin and uPA were expressed at lower levels in trophoblast from abortion patients (Figure A) than normal pregnant women, and decreased level of these molecules could hamper embryo implantation by interfering the trophoblast EMT process.…”
Section: Discussionsupporting
confidence: 61%
“…Many studies have shown that TGF-β can serve as a tumour suppressors to induce the expression of Smad7 and p21(CDKN1A) in certain cancers [55][56][57]. Interestingly, Smad7 and p21(CDKN1A) may act as components in a negative feedback regulation of TGF-β signalling, as Smad7 impedes TGF-β/Smad-driven transcription [21,58,59].…”
Section: Cesrp1 May Function As a Sponge Of Mir-93-5p In Sclcmentioning
confidence: 99%
“…After cell adhesion loss, cell polarity changes from apical‐substrate polarity to anterior‐posterior polarity, triggering cell migration and enhancing invasiveness. Epithelial‐mesenchymal transition as a new target of prime interest for anticancer metastasis and chemoresistance in breast cancer therapy has drawn great attention . Studies have shown that EMT biomarkers play a key role in breast cancer metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition as a new target of prime interest for anticancer metastasis and chemoresistance in breast cancer therapy has drawn great attention. 20,21 Studies have shown that EMT biomarkers play a key role in breast cancer metastasis. Families of the zinc-finger protein Snails (Snail1, Snail2, Snail3), the E-box-binding proteins Zebs (Zeb1, Zeb2), the basic helix-loop-helix protein Twists (Twist1, Twist2) directly inhibit the expression of E-cadherin in breast cells by directly binding to E-box of the proximal promoter of CDH1.…”
mentioning
confidence: 99%